Transformasi Pendidikan Menuju Keseimbangan Ekologi Melalui Inquiry Based Learning - Fitriane, Anisha Bunga Armethia; Nugraheni, Nursiwi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This article discusses the transformation of education towards ecological balance in the Sustainable Development Goals (SDGs) agenda. The aim of this article is to examine the transformation of conservation-based education towards ecological balance in the SDGS agenda. This research is qualitative-descriptive research using the library research method with research objects in the form of articles, books and research journals from the internet related to sustainable education, conservation character, inquiry-based learning, etc. The technique used to collect data is by analyzing previous articles according to the topic of discussion. The conclusions from this research show the importance of immediately implementing conservation education in learning and educators as the start or trigger of change.